Robot Pemantau Berbasis Internet Of Things Menggunakan Raspberry Pi - Rahmalia, Rahmalia; Nasir, Muhammad; Atthariq, Atthariq (Politeknik Negeri Lhokseumawe, 2022)
— In general, robots can be defined as a machine that is able to do human work either controlled or automatically. One of the human jobs that can be done by robots is the activity of monitoring the situation in dangerous places. The monitoring robot that is used here is a mobile robot that is able to move and can send video images captured by the camera which can then be controlled by the web controller. The purpose of designing this tool is to design a prototype monitoring robot that can move by being controlled via the web and displaying videos in real time wirelessly. In this design using the QoS method which method will measure the Qos parameters, namely Jitter and Delay by using the Wireshark application. As for other components that support the design of this robot is the access point that serves as a media link between the Raspberry Pi and the web, Raspberry Pi serves as a controller for monitoring robots and processing video images captured by the camera, the camera functions as an eye for monitoring robots and motor controllers function as a system that connects between raspberry pi and wheel drive in the form of a dc motor. The results of the analysis using QoS for video streaming on testing based on distances of 10, 50, and 100 meters have an average delay of 0.201 ms and jitter of 3.77 ms according to TIPHON is very good. The results of this study conclude that robots using internet of things (IoT) can be controlled remotely as long as the user has access to the internet network. Keywords: Robot, Quality of Service, Wireshark, Delay, Jitter, Internet of Things